Feasibility and acceptability of the 'Acutely Presenting Older Patient' screener in routine emergency department care. (18th May 2020) - Blomaard, Laura C; Mooijaart, Simon P; Bolt, Shanti; Lucke, Jacinta A; de Gelder, Jelle; Booijen, Anja M; Gussekloo, Jacobijn; de Groot, Bas
Abstract: Background: risk stratification tools for older patients in the emergency department (ED) have rarely been implemented successfully in routine care. Objective: to evaluate the feasibility and acceptability of the 'Acutely Presenting Older Patient' (APOP) screener, which identifies older ED patients at the highest risk of adverse outcomes within 2 minutes at presentation. Design and setting: 2-month prospective cohort study, after the implementation of the APOP screener in ED routine care in the Leiden University Medical Center. Subjects: all consecutive ED patients aged ≥70 years. Methods: feasibility of screening was assessed by measuring the screening rate and by identifying patient- and organisation-related determinants of screening completion. Acceptability was assessed by collecting experienced barriers of screening completion from triage-nurses. Results: we included 953 patients with a median age of 77 (IQR 72–82) years, of which 560 (59%) patients were screened. Patients had a higher probability of being screened when they had a higher age (OR 1.03 (95%CI 1.01–1.06), P = 0.017). Patients had a lower probability of being screened when they were triaged very urgent (OR 0.55 (0.39–0.78), P = 0.001) or when the number of patients upon arrival was high (OR 0.63 (0.47–0.86), P = 0.003). Experienced barriers of screening completion were patient-related ('patient was too sick'), organisation-related ('ED was too busy') and personnel-related ('forgot to complete screening'). Conclusion: with more than half of all older patients screened, feasibility and acceptability of screening in routine ED care is very promising. To further improve screening completion, solutions are needed for patients who present with high urgency and during ED rush hours.